IMPLEMENTATION OF MONETARY REFORMS IN KHIVA KHANATE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article examines the failure of monetary reforms in the Khiva Khanate, a significant political and economic entity in Central Asia. Despite its strategic location on the Silk Road and the potential for economic prosperity, the Khanate's rulers struggled to establish a stable and unified currency system. Key attempts at reform, including the introduction of the tanga coin, were undermined by internal issues such as political instability, currency debasement, and weak centralized control. External pressures, particularly from the expanding Russian Empire, further complicated these efforts. The article explores the broader economic, social, and political factors that contributed to the failure of these reforms, offering insights into the challenges of implementing effective monetary policy in a fragmented state.